Soziale Sicherung im Spannungsfeld gesellschaftlicher Transformation - Eine partizipative Studie in Küstendörfern der Fidschi-Inseln - Fink, Michael (Universitätsverlag Göttingen, 2016)
As other Pacific Islands Countries, Fiji is shaped by processes of social transformations and global environmental change. This study utilises ethnographic ideals for enhancing cultural and social geographic research in the global south. A participatory in-depth analysis of rural life in three Fijian coastal villages is at the core of this study. This is framed by a historic-political overview of the burden of Fiji's colonial past. Fijian coastal villagers are not passive victims of global social transformation and climate change. Through neo-traditional movements they actively form processes of social and cultural change. Rural Fijian norms, values and cultural identity crystallize in robust communities. Via modern forms of communication and transportation Fijians established globalised networks securing individuals' quality of life. Family members living far from their home villages remain in contact with their relatives. This way they keep their Fijian Identities as source of wellbeing and as well support the villagers' material wealth and knowledge to enhance capabilities. Merely regarding hazardous climate change impacts the passed on knowledge is spread abridged and poorly fitting into local value systems. Therefore, misperceptions and maladaptations are prevalent. In consequence this study pleads for development agencies to act culturally sensitive and to critically reflect ethnocentric worldviews in order not to harm Fijian values and wellbeing.